2008
DOI: 10.1099/vir.0.83341-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NS3 and NS5B proteins on classical swine fever virus internal ribosome entry site-mediated translation and its host cellular translation

Abstract: A full-length NS3 (NS3F) and a truncated NS3 protein (NS3H) with an RNA helicase domain possess RNA helicase activity. Using an in vitro system with a monocistronic reporter RNA or DNA, containing the CSFV 59-UTR, we observed that both NS3F and NS3H enhanced internal ribosome entry site (IRES)-mediated and cellular translation in a dose-dependent manner, but NS3 protease (NS3P) that lacks a helicase domain did not. NS3F was stronger than NS3H in promoting both translations. These results showed that viral RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Our previous studies revealed that the NS3 protein could promote CSFV IRES-mediated translation. The CSFV NS5B protein did not significantly affect IRES-directed translation alone, but significantly enhanced the stimulative effect of NS3 protein on IRES-mediated translation (Xiao et al, 2008). It has been reported that HCV NS5A protein downregulates HCV IRES-dependent translation (Kalliampakou et al, 2005).…”
Section: Classical Swine Fever Virus (Csfv) Is a Member Of The Genusmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies revealed that the NS3 protein could promote CSFV IRES-mediated translation. The CSFV NS5B protein did not significantly affect IRES-directed translation alone, but significantly enhanced the stimulative effect of NS3 protein on IRES-mediated translation (Xiao et al, 2008). It has been reported that HCV NS5A protein downregulates HCV IRES-dependent translation (Kalliampakou et al, 2005).…”
Section: Classical Swine Fever Virus (Csfv) Is a Member Of The Genusmentioning
confidence: 99%
“…The NS5B protein serves as the viral RNAdependent RNA polymerase (RdRp) (Steffens et al, 1999;Xiao et al, 2002) and contains a conserved GDD motif necessary for catalytic activity (Wang et al, 2007). NS3 is a multifunctional protein possessing serine protease, RNA helicase and nucleoside triphosphatase activities, and is important for virus replication and even for promoting viral and cellular translation (Gu et al, 2000; Piccininni et al, 2002;Sheng et al, 2007;Suzich et al, 1993;Warrener & Collett, 1995;Xiao et al, 2008; Xu et al, 1997). The 39UTR is probably involved in initiation of pestiviral genome replication (Isken et al, 2003(Isken et al, , 2004Pankraz et al, 2005;Xiao et al, 2004;Yu et al, 1999), whilst the 59UTR contains an internal ribosome entry site (IRES), located between nt 40 and 350 at the 59 terminus of the genome, which is able to facilitate translation of the viral genome (Fletcher & Jackson, 2002).…”
mentioning
confidence: 99%
“…Although genetic diversity in CSFV IRES elements was observed in this study, high conversation among these IRES sequences results in a stable secondary structure to facilitate an interaction between IRES elements and viral proteins. NS3 of CSFV can interact with the IRES element to increase translation initiation efficiency (Xiao et al, 2008;Zhu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These positive sense viral RNAs function similarly to mRNAs, but they contain the 5'-UTR, which exhibits extensive secondary structure features and multiple AUG codons preceding the initiation codon (Firth and Brierley, 2012). The extensive secondary structure plays an important role in IRES activity during the CSFV life cycle, as some CSFV and host cell proteins combine with the proper secondary structure for the IRES (Xiao et al, 2008;Zhu et al, 2010). The function of CSFV IRES is strongly influenced by the coding sequences immediately downstream of the initiation codon (Fletcher and Jackson, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, these proteins also play an important role in internal ribosome entry site (IRES)-mediated translation of CSFV. CSFV NS3 is a multifunctional protein possessing serine protease, RNA helicase, and nucleoside triphosphatase (NTPase) activities [81]. The RNA helicase activity of NS3 could promote viral and cellular translation, whereas the protease domain of NS3 interacted with NS5B to enhance viral translation [81].…”
Section: General Applications Of Live Cell Reporter Systems Reporter mentioning
confidence: 99%